Increasing the Learning Outcomes of Pkn Materials Knowing the Form of Joint Decisions Through Problem Based Learning Models - Putri, Yunita Dwi Nugrahani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to improve the results of learning Civics material to know the form of joint decisions through the problem based learning model in grade V SDN 03 kalisoro. Research subjects are researchers as students of class V second semester SDN 03 Kalisoro academic year 2021/2022 a number of 18. In the preliminary test before the class 72,72 cycle average with the percentage of 22,25% or 4 children experienced Increase in cycle I, with grade average 76,72 and percentage of mastery 66,67%. In cycle II, 3 children experienced an increase with grade average of 79,94 percentage 83,33% or 15 students have succeeded in reaching KKM. From the data indicate that student's learning result have an increase equal to 16,67%. Thus it was concluded that the problem-based learning model could improve the learning outcomes in Class V SDN 03 Kalisoro.